Creativity in successful eco-design supported by ten original guidelines. Issue 4 (2nd October 2021) - Maccioni, Lorenzo; Borgianni, Yuri; Pigosso, Daniela C.A.
ABSTRACT: To support the transition to sustainable development, eco-design must lead to the development of products that provide additional value when compared to traditional products, ultimately resulting in market success. In this study, creativity principles are explored as leverage points for eco-design implementation, enhancing customer acceptance and market success. The authors have inferred ten eco-design guidelines, which aim to enhance success chances in the development of new products. The proposed guidelines were verified through eco-ideation session and experts' evaluation. Results support the congruence of objectives between creativity, sustainability, success, and value creation in design. The guidelines represent a promising design tool to be further developed to pursue the objective of making eco-designed products more valuable and successful.